Meta Analysis: The Relationship of Looking Distance and Long Time of Smartphone use with Myopia - Robby, Muhammad; Hartoyo, Edi; Wydiamala, Erida; Husaini, Husaini; Arifin, Syamsul (Jurnal Berkala Kesehatan, 2024)
Myopia is a condition in which light strikes the retina, causing distant things to look blurry. There are over 285 million visually impaired persons worldwide, of whom 246 million are visually impaired and 39 million are blind. Therefore, a thorough investigation is required to assess the issue. Meta analysis is the study methodology employed. This study aimed to clarify the connection between the incidence of myopia the distance at which one stares and the amount of time spent on a smartphone. The review papers were selected from the collection's outcomes using Research Gate, Garuda Portal, and Google Scholar. The results of the review of research articles showed that there was a significant relationship between the distance of staring at a smartphone and the occurrence of myopia (p<0.00001) with a tendency for close distance staring at a smartphone to have a 0.29-fold risk of experiencing myopia compared to long distance staring at a smartphone. There was a significant relationship between the length of time using a smartphone and the occurrence of myopia (p<0.0001) with a tendency for a long time using a smartphone to have a 2.26-fold risk of experiencing myopia compared to not a long time using a smartphone.